2021
DOI: 10.7758/rsf.2021.7.2.06
|View full text |Cite
|
Sign up to set email alerts
|

Educational Place, Simultaneity, and Civic Participation in Asian America

Abstract: We thank the editors and anonymous reviewers for their helpful comments and suggestions. The article also benefited from generous comments provided by Janelle Wong, Luis Eduardo Guarnizo, and participants at the 2019 symposium on Asian Americans held at the Russell Sage Foundation in New York City. Finally, we thank Jennifer Lee and Karthick Ramakrishnan, for their vision and efforts in assembling this issue, and Suzanne Nichols, for keep us on track and sorted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Focus group research on Census participation revealed that lack of knowledge about the Census, such as the purpose and content of the survey and process of participation, was a barrier for several groups, including for Chinese, NHPI, and Vietnamese (Evans et al 2019). Barriers are particularly prominent for Asian immigrants who completed any education outside of the U.S., which appears to decrease civic participation, such as voting or volunteering (Chaudhary and Mai 2021). The impact was greater for some Asian American immigrant groups (Korean and Indian) and less apparent for others (Chinese and Vietnamese).…”
Section: Barriers and Challenges To Survey Participation For The Aanh...mentioning
confidence: 99%
“…Focus group research on Census participation revealed that lack of knowledge about the Census, such as the purpose and content of the survey and process of participation, was a barrier for several groups, including for Chinese, NHPI, and Vietnamese (Evans et al 2019). Barriers are particularly prominent for Asian immigrants who completed any education outside of the U.S., which appears to decrease civic participation, such as voting or volunteering (Chaudhary and Mai 2021). The impact was greater for some Asian American immigrant groups (Korean and Indian) and less apparent for others (Chinese and Vietnamese).…”
Section: Barriers and Challenges To Survey Participation For The Aanh...mentioning
confidence: 99%
“…In particular, many aspects affect immigrants’ integration to the host society such as language, employment, and presence of social networks. Research shows that immigrant participation in civic and political activities are low (Chaudhary & Mai, 2021; Desipio, 2011; Ramakrishnan & Viramontes, 2010). More than ever, it is critical for adult educators to facilitate connections between civic education and language learning to build the foundations for civic engagement and active citizenship.…”
Section: Civic Education In the Adult Esl Classroommentioning
confidence: 99%
“…Ali Chaudhary and Quan Mai (2021) shift the lens from policy attitudes to civic participation and examine variation within a racial group that is often perceived as only weakly engaged in U.S. politics. Much research on Asian American political participation has focused on the civic paradox of socioeconomic status (SES): even though Asian Americans have, on average, high levels of education and income, they have among the lowest levels of voting participation.…”
Section: The a R Ticles In This Is Suementioning
confidence: 99%